IMMUNOHISTOCHEMICAL FEATURES OF THE ENDOMETRIUM IN MISCARRIAGE - Matrizaeva Gulnara Djumaniyazovna; Ikhtiyarova Gulchekhra Akmalovna (Scholar Express Journals, 2022)
The problem of miscarriage continues to occupy one of the first places among the most important tasks of practical obstetrics and gynecology and is of great medical and social importance. Immunohistochemical and ultrastructural features of the endometrium in case of miscarriage are important for pathoanatomical diagnosis and gynecological practice. Data on the expression of steroid receptors, proteins that regulate the cell cycle, are important diagnostic signs of miscarriage
Keywords: endometrial immunohistochemistry; miscarriage; vascular endothelial growth factor